Impacto del uso del suelo sobre la condición de ribera en arroyos pampeanos y su relación con la estructura de la comunidad de peces - Granitto, María (2016)
In the last 30 years agricultural areas have occupied a larger proportion of cultivable zone in the Pampa Plain, generating the movement of livestock activities to the margins of waterways. These changes in land use can cause hydrological, morphological, physicochemical and biological alterations in the lotic systems of this region. The aim of this study is to evaluate the impact of different types of land use on the structure of the fish community in streams of the middle basin of Areco River. To do this, monthly samplings were realized during the summer of 2014 in four tributaries of the Areco River. Two of these sections were associated with an unfenced livestock use on the bank stream, while the other two sites had an agricultural use with preserved riparian zone. In each sampling site the structure of the riparian zone was evaluated by applying a quality index of the banks. On each sampling date physicochemical and hydrological parameters were surveyed and the fish community was sampled. The quality of the banks in places exposed to livestock was lower than in those dedicated to agricultural use. In the latter, the values of suspended solids were lower while the total coverage of macrophytes was higher. Moreover, the total fish biomass was higher in the sites with higher level of preservation of the riparian zone. Significant differences were also observed in the fish species composition among sites with contrasting land use. There were strong positive correlations between the proportion of piscivores and the integrity of the bank. These results show a consistent relationship between the land use and the quality of the bank, which ultimately have an impact on the structure of the fish community in the lotic systems of the Pampa Plain.